Estratégias de marketing via internet: estudo de caso com emissoras de rádio de Fortaleza - Bruno, Dilson Alexandre Mendonça (2007)
As the Internet plays an important role on modern living, it makes changes both customers and enterprises. And the broadcasting market also alters when listeners and companies take new possibilities on the development of virtual world. As a result of it, managers have already assessed their strategies to the Internet use, mainly on the way to make their marketing. With the theme Marketing Strategies Via Internet, this dissertation registers a multiple study of case carried out with four broadcasting companies in Fortaleza city, which performs on the segment of young people. And outcomes point out to variety setting when the theme is the use of electronic marketing (E-Marketing). It is verified, for example, the existence of an sender whom not yet it desires to invest in the Internet, for distrust to lose hearing and for not to consider the appropriate moment; another one already thinks about investing more fort in action of marketing for the net, although not to have initiated these changes in the practical one; one third sender is affiliated to the one strategical national net and no decision are not taken local; while it has an example of a radio that already was born strategically come back toward Internet, also, carrying through its action of marketing of electronic form. Also one evidences that the senders use the Internet mainly as tool of promotion of the made up of marketing, with emphasis in the spreading of sender through its sites. Although to recognize that web innovated the form to interact with its listeners, the Interactivity it is carried through of form limited for the studied senders. They not they possess, for example, politics defined for use of Interactivity in the elaboration and maintenance of data bases efficient or for the accomplishment of research to know better its public. Under the point of view of the Internet as surrounding for accomplishment business-oriented electronic (E-Business), the managers not they are stimulated. They point the advertiser absence and costs with the Internet as main limitors so that its sites give financial return currently. However, responsible for the senders they show good expectations for accomplishment business-oriented electronic in the future. Although the uncertainties, the Internet, in the generality, is not seen by the managers as a threat but rather as a tool that supports the radio that we know today. It is common sense between them that the conviviality of the radio with the Internet is inevitable.